Efficacy and safety of stem cell therapy in cerebral palsy: A systematic review and meta-analysis - Qu, Jiayang; Zhou, Lin; Zhang, Hao; Han, Dongmiao; Luo, Yaolin; Chen, Junming; Li, Lincai; Zou, Zhengwei; He, Zhengyi; Zhang, Minhong; Ye, Junsong (Frontiers in Bioengineering and Biotechnology, 2022)
Aim: Although the efficacy and safety of stem cell therapy for cerebral palsy has been demonstrated in previous studies, the number of studies is limited and the treatment protocols of these studies lack consistency. Therefore, we included all relevant studies to date to explore factors that might influence the effectiveness of treatment based on the determination of safety and efficacy. Methods: The data source includes PubMed/Medline, Web of Science, EMBASE, Cochrane Library, from inception to 2nd January 2022. Literature was screened according to the PICOS principle, followed by literature quality evaluation to assess the risk of bias. Finally, the outcome indicators of each study were extracted for combined analysis. Results: 9 studies were included in the current analysis. The results of the pooled analysis showed that the improvements in both primary and secondary indicators except for Bayley Scales of Infant and Toddler Development were more skewed towards stem cell therapy than the control group. In the subgroup analysis, the results showed that stem cell therapy significantly increased Gross Motor Function Measure (GMFM) scores of 3, 6, and 12 months. Besides, improvements in GMFM scores were more skewed toward umbilical cord mesenchymal stem cells, low dose, and intrathecal injection. Importantly, there was no significant difference in the adverse events (RR = 1.13; 95%CI = [0.90, 1.42]) between the stem cell group and the control group. Conclusions: The results suggested that stem cell therapy for cerebral palsy was safe and effective. Although the subgroup analysis results presented guiding significance in the selection of clinical protocols for stem cell therapy, high-quality RCTs validations are still needed.